Influence of Optical Feedback on Frequency Response of GaAs / AlGaAs Quantum Cascade Laser - Ragheed M. Ibrahim; Erada A. Al-Dabbagh (College of Education for Pure Sciences, 2010)
Abstract A theoretical analysis of the optical feedback from external reflector influence on the Frequency response of GaAs/Al0.45Ga0.55As triple quantum well Quantum Cascade Laser emitting at (l=9 mm) is presented. The employed theoretical model was based on Schrodinger equation. To demonstrate the effects of external cavity, many of the external cavity parameters were controlled such as the length of the external cavity, the proportion of optical feedback and the relative phase difference.